Risk factors and traditional Chinese medicine syndromes of mild cognitive impairment in community-dwelling hypertensive older adults - Gao, Jie; Wu, Meirong; Jia, Siyuan; Tian, Yuan; Wang, Dengkun; Lei, Xiaojing; Diwu, Yongchang (Frontiers in Public Health, 2025)
BackgroundHypertension is recognized as a risk factor for cognitive impairment in older adults. This study aimed to investigate the prevalence, associated factors, and traditional Chinese medicine (TCM) syndrome elements of mild cognitive impairment (MCI) among hypertensive older adults within Chinese communities.MethodsA community-based cross-sectional study was conducted involving hypertensive individuals. Participants were diagnosed with hypertension through medical history and physical examination, and were assessed for MCI using neuropsychological scales. TCM syndrome elements were evaluated using the Dementia Syndrome Scale. Logistic regression analysis was employed to identify risk factors for MCI and associated TCM syndromes.ResultsThe prevalence of MCI among 715 hypertensive participants was found to be 35.4%. Multivariate logistic regression analysis revealed sleep disorders as a significant risk factor for MCI (OR = 3.855, 95% CI: 2.454–6.055). Conversely, a higher education level, mental work, antihypertensive medication, and healthy lifestyle habits—including frequent tea consumption, reading, social interaction, and daily exercise—were identified as protective factors against MCI. TCM syndrome analysis indicated that marrow-deficiency, internal-heat, and phlegm-turbidity were significantly associated with an increased risk of MCI.ConclusionThe prevalence of MCI is high among older adults hypertensive individuals in Chinese communities, influenced by a combination of risk and protective factors. Sleep disorders represent a major risk factor, while modifiable lifestyle and medical factors serve as protective elements. Marrow-deficiency, internal-heat, and phlegm-turbidity are key TCM syndrome elements related to MCI. These findings underscore the importance of dynamic cognitive assessment in hypertensive patients and suggest personalized interventions that integrate both Western and TCM approaches for the prevention and management of MCI.